2022
DOI: 10.3390/ijerph192013102
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Healthcare Employees’ Burnout through Ethical Leadership: The Role of Altruism and Motivation

Abstract: Globally, employee burnout (EBO) is a black swan in healthcare management. Previous organizational management literature shows that EBO was often misunderstood by assuming it as a personal issue. However, the new definition by the World Health Organization (WHO) clearly indicates that EBO is an occupational phenomenon that places responsibility on organizations to manage it. Although recent evidence suggests ethical leadership (ELP) style may be important to mitigate EBO, shockingly, such relationships were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…14,18,41,42 Therefore, there is a need to further developing our empirical knowledge of ethical leadership in healthcare environments in the post-pandemic context. 8,41,43,44 Adding to the yet conceptually grounded view on ethical leadership, a similar effect is observed in the discussions of the effect of the workplace happiness of healthcare professionals in the quality of care delivered to patients. 34,[36][37][38] Therefore, this work addresses the imposing research questions: RQ1a: Does ethical leadership positively influence the social networks of healthcare professionals?…”
Section: Highlightsmentioning
confidence: 80%
See 2 more Smart Citations
“…14,18,41,42 Therefore, there is a need to further developing our empirical knowledge of ethical leadership in healthcare environments in the post-pandemic context. 8,41,43,44 Adding to the yet conceptually grounded view on ethical leadership, a similar effect is observed in the discussions of the effect of the workplace happiness of healthcare professionals in the quality of care delivered to patients. 34,[36][37][38] Therefore, this work addresses the imposing research questions: RQ1a: Does ethical leadership positively influence the social networks of healthcare professionals?…”
Section: Highlightsmentioning
confidence: 80%
“…Similarly, it is important to uncover its contributions to the quality of healthcare professionals' social networks given the overreliance on communication and development enforced by such leadership type. Considering the discussed literature review on ethical leadership, suggesting a positive effect on both individual and organizational level outcomes in healthcare organisations, 8,[41][42][43][44] we propose that: H1. Ethical leadership has a positive and direct impact on social networks existing among healthcare professionals.…”
Section: Highlightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, research on leadership styles in hospitals showed that transformational leadership behaviors from supervisors and management led to higher performance (Wu et al, 2022). The results indicated that intellectual stimulation and individualized consideration (dimensions of transformational leadership) were positively associated with branch sales performance.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Despite the abundance of research on the positive consequences of ethical leadership, there is a need to explore its role in enhancing both job burnout and broader psychological well-being [ 9 , 10 , 57 ], especially in the context of the healthcare [ 12 , 20 , 21 , 22 , 58 ]. This study aims to build on this foundation by examining the direct and indirect effects of ethical leadership on employee well-being within the context of public healthcare organizations.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%